Impacts of Financial Inclusion and Life Insurance Products on Poverty in Sub-Saharan African (SSA) Countries - Oladotun Larry Anifowose; Bibi Zaheenah Chummun (Risks)
In recent years, scholars have been paying more attention to financial inclusion, which has been positioned as a crucial component in accomplishing the majority of the seventeen Sustainable Development Goals set forward by the United Nations. Investigating the effects of life insurance and financial inclusion on poverty in 45 Sub-Saharan African (SSA) nations between 1999 and 2023 is the goal of this study. Using the Panel Autoregressive Distributed Lag (P-ARDL) method, this study concludes that poverty can be decreased through financial inclusion. Notably, we found that life insurance raises poverty when financial inclusion follows. This might be because there are not many microinsurance options available in SSA nations for those with low incomes. Due to their increased likelihood of being financially illiterate and their inability to purchase the necessary smart devices and internet services, the lower-income segments are unable to enjoy the same advantages as the higher-income segments. According to the findings, financial exclusion problems may be resolved by future life insurance, but this must be done in a sustainable manner. Future life insurance should address the requirements of the underprivileged and lower-income groups, and financial inclusion should be progressively enhanced.